(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Objective. To study the correlations between corneal distortion and morphological features in different kinds of eyes such as healthy ones (HE), ones previously undergone myopic PRK (PRKE), ones affected by keratoconus (KCE) and keratoconus eyes previously undergone corneal collagen crosslinking (CCCE). Materials and Methods. In this retrospective comparative study, a total of 106 HE of 106 patients, 58 PRKE of 58 patients, 33 KCE of 33 patients, 28 CCCE of 28 patients were included. A complete examination of all eyes was followed by tomographic (Pentacam, Oculus, Wetzlar, Germany) and biomechanical (Corvis ST, Oculus, Wetzlar, Germany) evaluation. Differences among Corvis ST (CST) parameters in the different groups have been analyzed. Linear regressions between central corneal thickness (CCT), intraocular pressure (IOP) and anterior corneal curvature measured with Simulated Keratometry (SK), versus corneal deformation parameters measured with Corvis ST in the different groups, have been run using SPSS software version 18.0. Results, HE showed a significant correlation between main curvature power of the cornea within the central 3 mm expressed in Diopters (KM) and 6 CST parameters; between CCT and 4 CST parameters and between IOP and 5 CST parameters. PRKE showed a significant correlation between KM and 3 CST parameters; between IOP and 4 CST parameters and none between CCT and CST parameters. KCE showed a significant correlation between SK and 3 CST parameters; between IOP and 3 CST parameters and none between CCT and CST parameters. CCCE showed a significant correlation between KM and 5 CST parameters; between CCT and 1 CST parameters and between IOP and 5 CST parameters. Discussion. Data of this study suggest that both corneal curvature and IOP could have a greater influence on the corneal deformation, compared to central corneal thickness (CCT). These results should be taken into account by further studies aiming to assess biomechanical corneal characteristics.